Fish for two - Bravo, Becky; Moss, Jason J. (Manila, Philippines : Lampara Publishing House, 2001)
Clara eats so much fish she starts to smell like one, so it isn't at all surprising when a dirty stray cat follows her home. But there's a problem: Clara hates cats!
In English and Tagalog.
Keywords: Children's stories